Approaching Rural Cults in the Conventus Cluniensis: Spaces, Agents and Contexts - Marco Simón, Francisco (ARYS. Antigüedad: Religiones y Sociedades, 2021)
This paper focuses on the rural cults documented in the Conventus Cluniensis (province of Hispania Tarraconensis. Starting from a conception of the sacred landscape as something "enchanted" and endowed with agency and in continuous transformation, the different places in which the relationship with the supernatural world is optimized are analysed: natural spaces (rock sanctuaries, sacred caves and forests, aquatic spaces) and others places whose sacred character is determined by votive epigraphy. Finally, the possible sanctuaries related to transhumance and livestock activities are considered, as well as the epigraphically attested agents, which belong mainly to the private sphere.
Keywords: Conventus Cluniensis; Hercules; Hispania Tarraconensis; rural cult; sanctuaries; votive epigraphy